Green, yellow, and red pigments in South American painting, 1610-1780 - Seldes, Alicia (2002)
A multidisciplinary team of chemists and art historians from the University of Buenos Aires and the National Council of Scientific and Technological Research (CONICET) has examined the green, yellow, and red pigments used in a collection of 29 paintings from the highlands of Peru in the Andean region during the colonial period (1610-1780). The results described in this paper are a continuation of previous research on blue pigments found in the same corpus (JAIC 38 [1999]: 100-23). The results show how the artists from the big workshops of Cusco and the cities of the Alto Peru (the highlands of Bolivia and N.W. Argentina) followed the recipes for color preparation included in the technical treatises written by Spanish painters. Once again, the figure of Mateo Pisarro, an artist active in the Puna of Atacama at the end of the 17th century, emerges as an exceptional investigator of color-rendering problems.